Insecticidal activity of three plants extracts against Myzus persicae (Sulzer, 1776) and their phytochemical screening - Billal NIA; Naama FRAH; Imane AZOUI (Acta Agriculturae Slovenica)
To reduce the use of synthetic pesticides and their negative effects on the environment, leaves extracts of Artemisia herba-alba Asso, Eucalyptus camaldulensis Dehnh and Rosmarinus officinalis L. were obtained with petroleum ether, ethanol and distilled water as solvents. These extracts were evaluated under laboratory conditions for their insecticidal effect against 3 to 4 days-old Myzus persicae individuals (Homoptera: Aphididae) at 1, 2.5, 5, and 10 %. We made observations after 24 hours. Etheric extract of all plants was effective and caused mortalities (100 %, 53 % and 60 % respectively) at the highest concentration. However, ethanolic and aqueous extracts did not show any significant insecticidal effect. The phytochemical screening showed the richness of etheric extract in terpenes. The results obtained suggest that we can make bioinsecticides based on leaves etheric extracts from these plants for use in integrated pest management.